Spectral identification of metallic minerals during high voltage pulse breakage by plasma emission spectroscopy - Rui Sun; Neng Wei; Xianqiang Wang; Liang Si; Weiran Zuo (Minerals Engineering, 2026)

Prelithiated sustained-release separators for high-capacity and stable lithium batteries - Juntao Si; Yida Wang; Yuexin Li; Rui Wang; Yixin He; Bicai Pan; Chunhua Chen (Chemical Engineering Journal, 2026)

Identifying global key regions where vapor pressure deficit dominates drought intensification - Yuxin Miao; Dehong Si; Zhijie Zheng; Yani Gun; Rui Li; Wanting Li; Wenzhang Sun; Dongfei Yang; Yaxin Li; Xinyue Wang; Guofeng Zhu (Global and Planetary Change, 2026)

FeCl3-catalyzed acetic acid pretreatment for surface-acetylated cellulose nanofibrils enabling Pickering emulsions and tunable optical composite films - Wei Liu; Xuan Wang; Rui Xu; Tairan Pang; Siyu Chen; Yuhan Liu; Ting Xu; Bo Pang; Haishun Du; Chuanling Si (Carbohydrate Polymers, 2026)

Corrigendum to “Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments” [Biores. Technol. 446 (2026) 134212] - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Tunnel crash injury severity across tunnel length grades: A bayesian hierarchical analysis of day/night context - Yangyang Xia; Chenzhu Wang; Rui Li; Said M. Easa; Kaihui Si; Pengyu Li; Meng Liu (Tunnelling and Underground Space Technology, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A dynamic pseudo-label driven dual-branch transformer framework for multi-scenario lake water body mapping - Kedi Fang; Bo Wang; Si Chen; Huaqi Gu; Rui Xia; Hai Liu (Journal of Hydrology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

A novel (H/C-CdS)/Zn5(OH)6(CO3)2 composite material with abundant adsorption sites and sulfur vacancies for highly effective tetracycline removal based on synergistic adsorption-visible photocatalysis - Rui Cao; Yuchang Wang; Xuewei Lang; Xiaoyu Wang; Yun Li; Huayan Si; Jianbin Zhang (Fuel, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Synergistic regulation of photosynthetic efficiency at physiological and transcriptional levels in Ottelia acuminata under single and combined nitrogen and phosphorus treatments - Xiong-Li Zhou; Ni-Fei Dai; Si-Qi Wang; Rui-Zhang; Zhen-Yu Lyu; Erik Jeppesen; Liu Yang; Shi-Kang Shen (Bioresource Technology, 2026)

Smog chamber study on the NOx dependence of SOA from isoprene photo-oxidation: Implication on RO2 chemistry - Xinbei Xu; Gehui Wang; Yining Gao; Si Zhang; Luyao Chen; Rongjie Li; Zheng Li; Rui Li (Journal of Environmental Sciences, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

Multichannel charge separation induced by multiple internal electric fields in ReS2/CoSx/CdS hollow nanostructures for efficient photocatalysis - Qi-Rui Zhang; Yu-Long Wang; Zhi-Hao Deng; You-Long Chen; Si-Jing Ding; Liang Ma (Journal of Environmental Chemical Engineering, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Effect of combined treatment of pH-shifting and mild heating on gel properties of transglutaminase induced cold-set peanut protein isolate gel - Jing Chen; Si Qiu; Rui Li; Zining Fan; Yu Wang; Yuntao Wang (Food Research International, 2025)

Lithium nitrate-stabilized electrolyte enabling wide-temperature and high-voltage lithium-ion batteries - Zhaojun Liu; Jiaxuan Feng; Rui Yang; Shen-ao Wang; Xiaochen Wu; Xiangyu Zhang; Sujuan Cheng; Ning Liu; Teng Long; Pengchao Si (Chemical Engineering Journal, 2025)

Effect of Manure Application on Few Soil Properties and Crop Yield Under Greenhouse Cultivation-a Comprehensive Analysis - You Wu; Jiale Zhang; Wei Si; Rui Liu; Zhenxin Qiu; Jianhua Yang; Renlei Luo; Xin Lei; Weiqi Wang; Musa Ma; Xinhao Yang; Cheng Yang (Journal of Soil Science and Plant Nutrition, 2025)

Wheat straw incorporation and nitrogen fertilization increase antibiotic resistance gene abundance and dissemination potential in agricultural soil - Feng-Hua Wang; Rui-Ao Ma; Zi-Teng Liu; Xin-Di Zhao; Ruibo Sun; Wenxu Dong; Yuming Zhang; Min Qiao; Si-Yu Zhang (Soil Ecology Letters, 2025)

Changes in gas-to-aerosol-phase partitioning ratio of semi-volatile products affect secondary organic aerosol formation from α-pinene photooxidation - Shijie Liu; Xinbei Xu; Si Zhang; Rongjie Li; Zheng Li; Can Wu; Rui Li; Feiyong Chen; Guiqin Zhang; Gehui Wang (Atmospheric Environment, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Interactions and feedback mechanisms in oasis wetland hydrology–soil–vegetation systems, northwestern China - Bing Liu; Ying Zhao; Arash Malekian; Xiao Wang; Wenzhi Zhao; Maliheh Behrang Manesh; Bin Wang; Changkun Yang; Weihao Sun; Wen Li; Pouyan Dehghan Rahimabadi; Yangyang Meng; et al. (CATENA, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Enhancement of soil DOC and electron transport by biochar strengthens Cd immobilization via iron oxides transformations in waterlogged soils - Xin Chen; Tianren Si; Senhan Wang; Rui Yuan; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Oral HMPB/Mn3O4 nanozymes for the treatment of ulcerative colitis via cellular redox balance regulation, gut microbiota modulation, and ferroptosis inhibition - Han Wang; Yexin Liu; Rui Huang; Weirui Chen; Luxuan Chen; Huacai Shi; Si Lei; Qi He; Ri Chen; Lihua Zhou; Wenxia Wang; Yanling She (Chemical Engineering Journal, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Comparison of annealing and heat-moisture modification on effects of Tartary buckwheat starch under plasma-activated water condition - Huilong Sang; Rui Zhang; Ruiyang Gao; Si Zhang; Hang Liu; Jianfei Pei; Jiamei Wang; Shanshan Gao (Food Chemistry, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

Synergistic adsorption-catalysis system based on the advanced oxidation technology of single-atom MOFs: Selective degradation and contribution to different ionization potential pollutants - Si-Han Zhou; Rui-Dong Wang; Yun Yang; AiJin Xiao; Xuejun Pan; Feng-zhi Jiang (Chemical Engineering Journal, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

Transcriptome profiling in peanut (Arachis hypogaea) in response to biotic stress produce by Bacillus amyloliquefaciens TA-1 - Wang Chen; Taswar Ahsan; Di Han; Wen-Rui Wang; Si-Tong Du; Chao-Qun Zang; Yu-Qian Huang; Ejaz Hussain Siddiqi (Plant Gene, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Grid shielding of interphase hybrids via spatial charge separation for regulating interfacial Zn redox kinetics - Ke Chen; Kun Rui; Wenhao Si; Huinan Wang; Cong Zhao; Yan Yan; Huijuan Lin; Jixin Zhu (Chemical Engineering Journal, 2025)

Effect of carrageenan on stability and 3D printing performance of high internal phase pickering emulsion stabilized by soy protein isolate aggregates under neutral condition - Rui Li; Xiuqin Guo; Pengfei Liu; Yuanyuan Li; Si Qiu; Yuntao Wang (Carbohydrate Polymers, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Carboxymethyl chitosan coating infused with linalool-loaded molten globular β-Lactoglobulin nanoparticles for extended preservation of fresh-cut apples - Xiaotong Wang; Junxiang Zhu; Tianjin Tang; Lei Yang; Xingyu Chen; Si Meng; Rui Zheng; Hao Wu (Food Chemistry, 2024)

Effects of single or conjoint administration of poly-β-hydroxybutyrate and Bacillus subtilis on growth, antioxidant capacity and apoptosis of common carp (Cyprinus carpio) - Liang Li; Yin-Tao Wang; Si-Tong Meng; Xiao-Fang Wei; Zhi-Yong Yang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Animal Feed Science and Technology, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Mechanisms underlying mitochondrial dysfunction and intestinal damage induced by ingestion of microplastics in Leuciscus waleckii: The role of the NF-κB/Nrf2 signaling pathway - Si Ying Liu; Deng Lai Li; Rui Zhu; Si Tong Meng; Yin Tao Wang; Liang Li; Zhi Yong Yang; Li Fang Wu (Chemosphere, 2024)

Iron-modified biochars and their aging reduce soil cadmium mobility and inhibit rice cadmium uptake by promoting soil iron redox cycling - Tianren Si; Xin Chen; Rui Yuan; Siyu Pan; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2024)

Effects of replacing fish meal with biofloc meal on growth performance, nutrients metabolism, immune response and intestinal microbiota of common carp (Cyprinus carpio) - Xiao-Fang Wei; Si-Tong Meng; Yin-Tao Wang; Liang Li; Rui Zhu; Deng-Lai Li; Si-Ying Liu; Li-Fang Wu (Aquaculture, 2024)

Multifunctional Ni-MOF (3D) with N-rich structures for self-generated reactive oxygen species and enhanced electron transfer for synergistic degradation of organic pollutants and removal of Hg(II) - Si-Han Zhou; Rui-Dong Wang; Yun Yang; Hui-ying Li; Li-jun Luo; Feng-zhi Jiang (Journal of Cleaner Production, 2024)

Visible light assisted periodate activation with porous C3N5 for tetracycline degradation: Enhanced electron-hole separation and reactive oxygen species formation - Sitong Liu; Shicheng Liu; Taojin Wang; Letong Yang; Letao Li; Xiaodong Wu; Zhichun Si; Rui Ran; Hui Wu (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Effect of chitooligosaccharides in inhibiting textural deterioration of chicken myofibril protein gel induced by high temperature - Yuntao Wang; Jing Chen; Rui Li; Shasha Wang; Ke Li; Yu Wang; Si Qiu; Dianbo Zhao; Yanhong Bai (Food Hydrocolloids, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Impact of high-altitude environments on the motion and settling characteristics of wet-mix shotcrete dust in tunnels - Guoliang Zhang; Zhongan Jiang; Xiaocuan Li; Ya Chen; Bin Yang; Mingli Si; Rui Feng; Ming Wang (Tunnelling and Underground Space Technology, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Evaluate the groundwater quality and human health risks for sustainable drinking and irrigation purposes in mountainous region of Chongqing, Southwest China - Rui Li; Yuting Yan; Jiaqian Xu; Chang Yang; Si Chen; Yangshuang Wang; Yunhui Zhang (Journal of Contaminant Hydrology, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Enhancing soil redox dynamics: Comparative effects of Fe-modified biochar (N–Fe and S–Fe) on Fe oxide transformation and Cd immobilization - Tianren Si; Rui Yuan; Yanjie Qi; Yuhao Zhang; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Environmental Pollution, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Effect of konjac glucomannan with different degrees of deacetylation on the gel behavior of transglutaminase induced soybean protein isolate emulsion gels - Yuntao Wang; Hui Zhang; Qing Liang; Xiuqin Guo; Zijian Niu; Si Qiu; Wei Xu; Rui Li (Food Hydrocolloids, 2024)

Chlorogenic acid improves common carp (Cyprinus carpio) liver and intestinal health through Keap-1/Nrf2 and NF-κB signaling pathways: Growth performance, immune response and antioxidant capacity - Guo-Jun Shang; Si-ying Liu; Rui Zhu; Deng-Lai Li; Si-Tong Meng; Yin-tao Wang; Li-Fang Wu (Fish & Shellfish Immunology, 2024)

Effects of poly-β-hydroxybutyrate on growth, antioxidant capacity and lipid metabolism of common carp (Cyprinus carpio) under waterborne copper exposure - Liang Li; Yin-Tao Wang; Si-Tong Meng; Xiao-Fang Wei; Zhi-Yong Yang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Aquaculture, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Nutrient-rich hydrothermal carbon production by exogenous nutrients combined with seaweed internal water - Jikai Lu; Rui Wang; Bing Wang; Xu Xia; Kenji Ogino; Junlin Huang; Hongyu Si (Journal of Environmental Management, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Shear wave velocity structure of the upper crust in north Xiaojiang fault zone in SE Tibet via short-period ambient noise dense seismic array - Si Chen; Rui Gao; Zhanwu Lu; Yao Liang; Wei Cai; Lifu Cao; Zilong Chen; Guangwen Wang (Physics of the Earth and Planetary Interiors, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Rape straw biochar enhanced Cd immobilization in flooded paddy soil by promoting Fe and sulfur transformation - Rui Yuan; Tianren Si; Qingquan Lu; Rongjun Bian; Yan Wang; Xiaoyu Liu; Xuhui Zhang; Jufeng Zheng; Kun Cheng; Stephen Joseph; Lianqing Li; Genxing Pan (Chemosphere, 2023)

A superstable, flexible, and scalable nanofluidic ion regulation composite membrane - Lianmeng Si; Yihan Wu; Hong Xiao; Wensi Xing; Rui Song; Yiju Li; Sha Wang; Xu Liang; Wenshan Yu; Jianwei Song; Shengping Shen (Science Bulletin, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

The impact of behavior safety management system on coal mine work safety: A system dynamics model of quadripartite evolutionary game - Yan Zhang; Si-Xia Wang; Jian-Ting Yao; Rui-Peng Tong (Resources Policy, 2023)

Structural incorporation of iron influences biomethylation potential of mercury sulfide - Yunyun Ji; Shan Gao; Rui Si; Zhanhua Zhang; Li Tian; Wenyu Guan; Weichao Wang; Jiubin Chen; Wei Chen; Pedro J.J. Alvarez; Tong Zhang (Geochimica et Cosmochimica Acta, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Examination of the transmission mechanism of energy prices influencing carbon prices: an analysis of mediating effects based on demand heterogeneity - Rui Wang; Xinglin Zhao; Kerong Wu; Sha Peng; Si Cheng (Environmental Science and Pollution Research, 2023)

Upcycling corn straw into nanocelluloses via enzyme-assisted homogenization: Application as building blocks for high-performance films - Hongbin Yang; Long Bai; Yaxin Duan; Hongxiang Xie; Xumei Wang; Rui Zhang; Xingxiang Ji; Chuanling Si (Journal of Cleaner Production, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Tectono-sedimentary evolution of the Paleogene Qikou Sag, Bohai Bay Basin, NE China - Si Chen; Rui Zhao; Changwei Chen; Hua Wang; Jianghao Ma; Tianhao Gong; Zhenghong Yu (Marine and Petroleum Geology, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Increasing role of phenolic oxidative branch in daytime oxidation process of aromatics in Chinese haze period - Fanglin Wang; Xiaodi Liu; Shaojun Lv; Si Zhang; Can Wu; Shijie Liu; Yali Lei; Yubao Chen; Rui Li; Gehui Wang (Science of The Total Environment, 2023)

Can green finance promote urban green development? Evidence from green finance reform and innovation pilot zone in China - Hongfeng Zhang; Yixiang Wang; Rui Li; Hongyun Si; Wei Liu (Environmental Science and Pollution Research, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Bivariate copula function-based spatial–temporal characteristics analysis of drought in Anhui Province, China - Rui Wang; Chunli Zhao; Jiquan Zhang; Enliang Guo; Danjun Li; Si Alu; Si Ha; Zhenhua Dong (Meteorology and Atmospheric Physics, 2019)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Paleogene sedimentation changes in Lenghu Area, Qaidam Basin in response to the India–Eurasia collision - Rui Zhao; Si Chen; Hua Wang; Detian Yan; Haiyang Cao; Yin Gong; Jie He; Zhixiong Wu (International Journal of Earth Sciences, 2019)

Integrated drought risk assessment of multi-hazard-affected bodies based on copulas in the Taoerhe Basin, China - Rui Wang; Jiquan Zhang; Enliang Guo; Si Alu; Danjun Li; Si Ha; Zhenhua Dong (Theoretical and Applied Climatology, 2019)

A new isoflavanone from Ficus tikoua Bur - Si-Yu Zhou; Rui Wang; Li-Qing Deng; Xiao-Long Zhang; Min Chen (Natural Product Research, 2018)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Assessing non-linear variation of temperature and precipitation for different growth periods of maize and their impacts on phenology in the Midwest of Jilin Province, China - Enliang Guo; Jiquan Zhang; Yongfang Wang; Si Alu; Rui Wang; Danjun Li; Si Ha (Theoretical and Applied Climatology, 2018)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Efficacy and safety of escitalopram in treatment of severe depression in Chinese population - Tianmei Si; Gang Wang; Fude Yang; Yiru Fang; Maosheng Fang; Jijun Li; Jicheng Dong; Xinhua Shen; Jianmin Zhuo; Qing Rui; Jinan Wang; Hu Cuili (Metabolic Brain Disease, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)